Negotiating Transgender Identity Amidst Increasing Cases of Discrimination in Donald Trump’s Presidency - Isna Ardyani Fataya (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
In contemporary society, transgender become a controversial issue since people consider the attitude violates binary gender. As transgender organization to obtain equal rights grew larger, discriminations against transgender ironically grew larger. This research aims at investigating factors which trigger the rise of discrimination cases against transgender in Donald Trump’s presidency. It also analyzes efforts of transgender people to negotiate their identity in the midst of discrimination. This research employs descriptive qualitative method with the source of data are taken from U.S online newspaper, The New York Times from 2017 to 2020 throughout Trump’s presidency. The study reports that the increasing cases of discrimination against transgender are perpetuated by Trump’s anti-LGBT policies, racist and sexist attitude, religious Christian belief. In addition, transgender have ways to negotiate public discrimination by concealing gender identity and modifying gender expression such as by changing legal name, pronoun, clothing, voice, and mannerism.